Imbalances in the Hsp90 Chaperone Machinery: Implications for Tauopathies - Shelton, Lindsey B.; Koren, John; Blair, Laura J. (Frontiers in Neuroscience, 2017)
The ATP-dependent 90kDa heat shock protein, Hsp90, is a major regulator of protein triage, from assisting in nascent protein folding to refolding or degrading aberrant proteins. Tau, a microtubule associated protein, aberrantly accumulates in Alzheimer’s disease (AD) and other neurodegenerative diseases, deemed tauopathies. Hsp90 binds to and regulates tau fate in coordination with a diverse group of co-chaperones. Imbalances in chaperone levels and activity, as found in the aging brain, can contribute to disease onset and progression. For example, the levels of the Hsp90 co-chaperone, FK506-binding protein 51 kDa (FKBP51), progressively increase with age. In vitro and in vivo tau models demonstrated that FKBP51 synergizes with Hsp90 to increase neurotoxic tau oligomer production. Inversely, protein phosphatase 5 (PP5), which dephosphorylates tau to restore microtubule-binding function, is repressed with aging and activity is further repressed in AD. Similarly, levels of cyclophilin 40 (CyP40) are reduced in the aged brain and further repressed in AD. Interestingly, CyP40 was shown to breakup tau aggregates in vitro and prevent tau-induced neurotoxicity in vivo. Moreover, the only known stimulator of Hsp90 ATPase activity, Aha1, increases tau aggregation and toxicity. While the levels of Aha1 are not significantly altered with aging, increased levels have been found in AD brains. Overall, these changes in the Hsp90 heterocomplex could drive tau deposition and neurotoxicity. While the relationship of tau and Hsp90 in coordination with these co-chaperones is still under investigation, it is clear that imbalances in these proteins with aging can contribute to disease onset and progression. This review highlights the current understanding of how the Hsp90 family of molecular chaperones regulates tau or other misfolded proteins in neurodegenerative diseases with a particular emphasis on the impact of aging.